Viabilitas Benih dan Vigor Bibit Kakao (Theobroma cacao L.) Berdasarkan Kondisi Air pada Media Tanam dan Kedalaman Tanam Benih - Agam Ihsan Hereri; Erida Nurahmi; Nur Zahara (Jurnal Agrista, 2009)
Seed Viability and Form of Seedling Cocoa (Theobroma cacao L.) Condition Based on Moisture Media Planting and Deep SeededABSTRACT. Plant that have a high productivity has always started with the best planting material, both in the form of seeds or seedling. Agronomic inputs would be more optimal if the plants have optimum vigor. The aim of this study is to determine the effect of water on medium condition of seedlings and planting depth on seed viability and vigor of seedling of cacao. The result showed that the germination medium water conditions have no significant on all variables observed. While the depth of planting the seed in cultivation media has a very significant effect on potential germination, seedling vigor and dry weight, but no significant effect on height and weight of epicotyls weight wet. The best variables values found in the seeds are planted as deep as 4 cm from the surface of growing media. Besides seed viability and vigor of seedling planted at a depth indicated that different is not severely affected by the condition of water at planting media.